2008
DOI: 10.1002/art.23937
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate diminishes CCL2 expression in human osteoblastic cells via up‐regulation of phosphatidylinositol 3‐Kinase/Akt/Raf‐1 interaction: A potential therapeutic benefit for arthritis

Abstract: Objective. To assess the effects of epigallocatechin-3-gallate (EGCG) on oncostatin M (OSM)-induced CCL2 synthesis and the associated signaling pathways in human osteoblastic cells. The therapeutic effect of EGCG on collagen-induced arthritis (CIA) in rats was also studied.Methods. CCL2 and c-Fos messenger RNA expression was analyzed by Northern blotting. The modulating effects of EGCG on the activation of Raf-1, Akt, and phosphatidylinositol 3-kinase (PI 3-kinase) were examined by coimmunoprecipitation, Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 75 publications
5
44
0
1
Order By: Relevance
“…55 There have been mixed reports regarding the effects of EGCG on Akt depending on the cell type studied, as EGCG is shown to reduce Akt phosphorylation in endothelial cells, tumor associated endothelial cells and caco-2 cells, [56][57][58][59] but activate Akt in lung carcinoma cells and osteoblasts. 60,61 Here, we show that EGCG reduces Akt activation and subsequently inflammation in immune stimulated mesangial cells.…”
Section: Egcg Inhibits Inflammation In Lupus Mesangial Cellsmentioning
confidence: 65%
“…55 There have been mixed reports regarding the effects of EGCG on Akt depending on the cell type studied, as EGCG is shown to reduce Akt phosphorylation in endothelial cells, tumor associated endothelial cells and caco-2 cells, [56][57][58][59] but activate Akt in lung carcinoma cells and osteoblasts. 60,61 Here, we show that EGCG reduces Akt activation and subsequently inflammation in immune stimulated mesangial cells.…”
Section: Egcg Inhibits Inflammation In Lupus Mesangial Cellsmentioning
confidence: 65%
“…Primary cultures of human bone marrowderived osteoblasts were established from alveolar bone explants as previously described (30). Cells were maintained in induction media for the duration of the study, without serum starvation.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP was performed as described previously (30), using an assay kit from Upstate Biotechnology. Briefly, the DNA-protein complex from treated U2OS cells was crosslinked with 1% formaldehyde for 10 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained showed a significant correlation between the decrease in the levels of CRP, ESR, Rf, IL-6 and TNF-α in good and moderate green tea RA responders as compared to nonresponders, whereas the disease activity remained unchanged. These results demonstrated the antirheumatic activity of green tea which may be related to the antioxidant and anti-inflammatory of its phenolic compounds, especially catechins (Morinobu et al, 2008;Lin et al, 2008). Also, many studies reported that treatment of green tea reduced oxidative stress free radicals induced production of proinflammatory cytokines TNF-α, IL-6, CRP and NF-kB activation in a dose dependent manner (Kim et al, 2000;Wahyudi and Sargowo, 2007;Ramesh et al, 2009).…”
Section: Discussionmentioning
confidence: 76%